A new species of Paraphlomis (Lamiaceae) from Northern Luzon, Philippines - Tandang, Danilo N.; Calaramo, Michael Agbayani; Bucay, Mark Angelo C.; Obeña, Ren Divien R.; Angeles, Marjorie D. Delos (Phytotaxa, 2026)
Paraphlomis aristata, a perennial herbaceous plant belonging to the mint family (Lamiaceae), was discovered in Northern Luzon, Philippines, and is herein described and illustrated. The new species shares phenetic similarity with P. javanica in having a stem with quadrangular, obtuse corners, covered with fine hairs, and with elliptic leaves that are confined to the upper stem. In addition, the species have globose verticillaster inflorescences, and mature nutlets have a rounded apex. Paraphlomis aristata is notably differentiated by its light-yellow flowers with calyces that have a strongly involute margin, which are constantly densely villose on the abaxial surface throughout both flowering and fruiting stages. Moreover, the calyx lobes are narrowly triangular, each with a needle-like, filiform, or bristle-like apex.